Mechanical external work of a football season computed by GPS - Pavei, G.; Osgnach, C.; di Prampero, P. E. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: The (positive) mechanical external work (Wext) is the work performed by the muscle-tendon unit to accelerate and lift the body center of mass (Peyré-Tartaruga et al. 2021). It has historically been investigated in steady locomotion, where it was able to explain most of the absolute metabolic cost and its variations (Peyré-Tartaruga et al. 2021). In recent years the mechanical approach has been applied also to unsteady locomotion (e.g. shuttle and sprint running) typical of team sports (Zamparo et al. 2019; Pavei et al. 2019) albeit still using optoelectronic systems, which is a standard for computation, but an unfeasible approach during team sports training or competitions.